Lifecycle-based feasibility indicators for floating solar photovoltaic plants along with implementable energy enhancement strategies and framework-driven assessment approaches leading to advancements in the simulation tool - Kumar, Nallapaneni Manoj; Islam, Sayemul; Podder, Amit Kumer; Selim, Ali; Bajaj, Mohit; Kamel, Salah (Frontiers in Energy Research, 2023)
Floating solar photovoltaic (FSPV) systems that allow solar panel installations on water bodies are gaining popularity worldwide as they mainly avoid land-use conflicts created by, and for their superior performance over, ground-mounted photovoltaic installations. Though many studies in the FSPV literature showed how superior FSPVs perform, we still believe there are few potential opportunities for further enhancement in performance. On the other side, the industry’s delivery of FSPV installation service to clients is often questioned, highlighting that FSPV modeling is compromised, leading to false promises on energy performance and feasibility. This might be true given the lack of modeling tools specific to FSPV. With this hypothesis, this review investigates existing modeling approaches by FSPV researchers/industry people practicing and potentially implementable energy performance enhancement strategies leading to the advancement of modeling tools. The review outcome suggested that every FSPV researcher/service provider must carefully design and optimize the FSPV system considering suitable performance enhancement strategies, for instance, replacing conventional solar panels with bifacial ones and integrating various cooling and cleaning methods. Also, while assessing the feasibility, they must follow the lifecycle-based performance indicators that broadly fall under the techno-economic-environmental and social aspects with an appropriate framework-driven assessment approach. Lastly, we have shown a conceptual FSPV project simulation tool consolidating the performance indicators and explored performance enhancement strategies that we believe would help the FSPV community.